62.7k views
3 votes
Start with the graph of f(x) = 9x. Then write a function g(x) that results from the given transformation.reflect f(x) about the y-axisg(x) =

1 Answer

1 vote

The transformation of function and their algebraic representation are shown below:

From it we notice that to reflect the function about the y-axis we need to change the sign of the variable, then we have:


\begin{gathered} g(x)=9(-x) \\ g(x)=-9x \end{gathered}

Therefore, the expression of g is:


g(x)=-9x

Start with the graph of f(x) = 9x. Then write a function g(x) that results from the-example-1
User Darrow Hartman
by
5.5k points